Multiple Source Localization Based on Acoustic Map De-Emphasis. (26th December 2010) - Brutti, Alessio; Omologo, Maurizio; Svaizer, Piergiorgio
Abstract : This paper describes a novel approach for localization of multiple sources overlapping in time. The proposed algorithm relies on acoustic maps computed in multi-microphone settings, which are descriptions of the distribution of the acoustic activity in a monitored area. Through a proper processing of the acoustic maps, the positions of two or more simultaneously active acoustic sources can be estimated in a robust way. Experimental results obtained on real data collected for this specific task show the capabilities of the given method both with distributed microphone networks and with compact arrays.